Working conditions and innovative behaviors at work: an exploratory study of medical representatives in Côte d'Ivoire. - KONAN , Amoin Lucie; BAMBA , Affoué Akpo Sabine; GUEI , Desleu Jacques Aimé (Revue Internationale du Chercheur, 2025)
Abstract